1998
DOI: 10.1016/s0022-2275(20)32480-9
|View full text |Cite
|
Sign up to set email alerts
|

Low and high responders to pharmacological doses of β-carotene: proportion in the population, mechanisms involved and consequences on β-carotene metabolism

Abstract: The aim of this study was to assess the interindividual variability of chylomicron ␤ -carotene response to a pharmacological load of ␤ -carotene in the population, to identify the mechanisms responsible for this variability, and to evaluate its consequences on ␤ -carotene status and metabolism. The variability, as estimated by the 3-h chylomicron ␤ -carotene response to 120 mg ␤ -carotene in 79 healthy male volunteers, was high (CV ‫؍‬ 61%), but it was unimodal and all the subjects had detectable chylomicron ␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(26 citation statements)
references
References 50 publications
(77 reference statements)
3
23
0
Order By: Relevance
“…In these studies ␤-[ 14 C]carotene doses from 6 to 52 Ci were administered to lymph-cannulated patients with reported absorption values of 8-17% and one extreme at 52% (31,32). Our value of 42.6% ␤-carotene bioavailability is consistent with the prevailing concept (33,34) that ␤-carotene absorption is inefficient, even under favorable absorptive conditions. The fecal output of 14 C was biphasic (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In these studies ␤-[ 14 C]carotene doses from 6 to 52 Ci were administered to lymph-cannulated patients with reported absorption values of 8-17% and one extreme at 52% (31,32). Our value of 42.6% ␤-carotene bioavailability is consistent with the prevailing concept (33,34) that ␤-carotene absorption is inefficient, even under favorable absorptive conditions. The fecal output of 14 C was biphasic (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…As regards the first hypothesis, there are several lines of evidence that suggest retinyl ester secretion with hepatic VLDL: i) The observed parallelism between retinyl esters and ␤-carotene concentration-time course for 24 h postdosing suggests similar metabolism; this is significant because ␤-carotene undergoes hepatic resecretion with VLDL (45); ii) experiments in dogs have documented retinyl ester secretion from the liver (46); and iii) approximately 5-10% of the total vitamin A in fasting plasma is present in the form of retinyl esters and several studies have shown that retinyl esters can travel with hepatically derived VLDL and LDL (42,(47)(48)(49)(50). The second hypothesis of multiple inputs of ␤-carotene from the intestine due to a subsequent meal(s) and/or irregular secretion of lipid has been previously suggested (11,34). This phenomenon has been attributed to the relatively poor solubility of ␤-carotene in triglyceride (51,52), which leads to significant deposition of ␤-carotene within the enterocyte membrane.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, the highest responder had AUC of 5.20 and 4.18 lmolÁd/L and the lowest responder had AUC of 0.577 and 0.089 lmolÁd/L for the high and low b-carotene muffins, respectively. The phenomenon of low and high responders to b-carotene supplementation is well documented in the literature (27). Further studies should determine if this is due to differences in absorption, altered chylomicron metabolism ( 27), or differences in the ability to cleave b-carotene to vitamin A.…”
Section: Discussionmentioning
confidence: 97%
“…They have also been obtained with very variable doses of FSV&C, which were incorporated into different matrices and ingested in different meals. Knowing that i) FSV&C absorption is affected by numerous factors, including FSV&C dose, food matrix and meal nutrients [19], ii) absorption is probably mediated by intestinal proteins at dietary doses but is probably passive at pharmacological doses, and iii) there is a huge interindividual variability in the absorption efficiency of most FSV&C [62,63], all these factors likely explains the huge variability in published data.…”
Section: Absorption Efficiency (% Of a Given Dose)mentioning
confidence: 99%
“…On the whole, this review of the literature shows that it is difficult to provide a single narrow range for the absorption efficiency of each FSV&C in humans. This is likely because absorption of FSV&C is affected by numerous factors [19], but also because there is a huge inter-individual variability in the absorption efficiency of these molecules [62,63].…”
Section: 1)mentioning
confidence: 99%